Musculoskeletal Injuries in Table Tennis during Competition: A Systematic Review - Ko, Sang-Hun; Cha, Jae-Ryong; Lee, Chae-Chil; Kim, Min-Seok; Park, Ki-Bong (International Journal of Sports Medicine, 2023)
The study aimed to investigate the incidence of musculoskeletal injuries among table tennis players and identify their associated risk factors. We conducted a literature search in online databases using relevant search terms related to “table tennis” and “injury”. To compare the rate of injuries according to player-related variables, we extracted information on sex, level of games, circumstances of injury, and duration of sport absence after injury. Furthermore, we calculated the odds ratios based on the number of injuries according to variables. Eight articles included 873 professional table tennis players, revealing an overall musculoskeletal injury rate of 3.6% (31 musculoskeletal injuries). The incidence was 10.0 injuries per 1,000 playing hours (range, 0–27.0). The rate of musculoskeletal injuries for female and male players were 3.2% and 3.8%, respectively, and those for Summer Olympic Games, Asian Games, and domestic national games was 4.8%, 15.4%, and 0%, respectively. More than half (52%) of injuries occurred during training, and most injuries (64%) were of a nature that did not cause time loss. This review provides valuable information about the incidence of musculoskeletal injuries in table tennis competitions. However, owing to the limitations of this study in identifying injury-related risk factors, future studies analyzing comprehensive variables are required.
Keywords: knee; sport; trauma; sport medicine; exercise physiology; oxidative stress; aging; skeletal muscle; german; english; translation; table tennis; racketsports; physical education; minimum lactate; physiology; incidence; musculoskeletal injury; sport; editorial office